2009
DOI: 10.1186/1471-2407-9-45
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of MCP-1 and other paracrine factors in a novel tumor-bone coculture model

Abstract: BackgroundThe bone-tumor microenvironment encompasses unique interactions between the normal cells of the bone and marrow cavity and the malignant cells from a primary or metastasized cancer. A multitude of paracrine factors within this microenvironment such as the growth factor, TGF-β, and the chemokine, MCP-1, are secreted by many of these cell types. These factors can act in concert to modulate normal and malignant cell proliferation, malignant cell migration and invasion and, often, mediate bone cancer pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
2
16
1
Order By: Relevance
“…In keeping with other reports, we observed a decline in marrow viability after 48 hours as revealed by trypan blue exclusion measurement and appearance in histologic section [31]. An important next step will involve the systematic optimization of conditions for long-term culture.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In keeping with other reports, we observed a decline in marrow viability after 48 hours as revealed by trypan blue exclusion measurement and appearance in histologic section [31]. An important next step will involve the systematic optimization of conditions for long-term culture.…”
Section: Discussionsupporting
confidence: 89%
“…Schiller et al developed a model in which whole neonatal mouse femurs were co-cultured with a variety of mouse and human cancer cell lines, demonstrating bone tissue viability and illustrating synergistic paracrine interactions between intact bone and tumor cells with enzyme-linked immunosorbent assay (ELISA) [31]. Curtin et al developed a roller tube model system to co-culture mouse calvarial bones with breast and prostate cancer cell lines to demonstrate cancer cell colonization of the endosteal bone surfaces and subsequent promotion of osteoclast activity resulting in bone resorption [32].…”
Section: Discussionmentioning
confidence: 99%
“…Development of co- cultures with femur and cancer cells, up-regulate MCP-1 and TGFβ expression and secretion in sarcoma, but down-regulates MCP-1 and TGFβ expression and secretion in breast cancer cultures [85]. However, recent studies measuring cytokines and chemokines in vivo in a murine model of breast cancer demonstrated a significant increase in MCP-1, MIP-1A, IL-6 and TNFα [61].…”
Section: Mechanisms Of Cancer Painmentioning
confidence: 99%
“…CFPs were placed into transwell culture plates with control media, tumor-CM, or tumor-CM with the addition of MCP1 neutralizing antibody. Tumor-CM was harvested from the LLC, EMT-6 (murine mammary carcinoma) and K7M2 (murine osteosarcoma) tumor cell lines, all of which have been shown to produce MCP1 (data above and references 43,44 ). Analysis showed that exposure to conditioned media from each tumor line resulted in preferential migration of CFPs when compared with response of CFPs to control media ( Figure 11G, P Յ 0.05).…”
Section: Ddr2mentioning
confidence: 99%